Simultaneously Imaging an Inhomogeneous Conductive Medium and Various Impenetrable Obstacles (Journal of Computational Mathematics, 2025)
Consider the inverse scattering of time-harmonic acoustic waves by a mixed-type scatterer consisting of an inhomogeneous penetrable medium with a conductive transmission condition and various impenetrable obstacles with different kinds of boundary conditions. Based on the establishment of the well-posedness result of the direct problem, we intend to develop a modified factorization method to simultaneously reconstruct both the support of the inhomogeneous conductive medium and the shape and location of various impenetrable obstacles by means of the far-field data for all incident plane waves at a fixed wave number. Numerical examples are carried out to illustrate the feasibility and effectiveness of the proposed inversion algorithms.
Keywords: Inverse acoustic scattering; Modified factorization method; Numerical reconstruction; Inhomogeneous medium.